HUBUNGAN ANTARA PERAN JENIS DENGAN KOMPETENSI INTERPERSONAL PADA REMAJA - -, Apollo (Widya Warta, 2010)
This research was of three objectives: (a) to examine the relationship between sex role and interpersonal competence of adolescence, (b) to examine whether there was some difference of interpersonal competence of adolescence due to sex role, and (c) to examine whether there was some difference of interpersonal competence of adolescence due to gender. The sample of this research was 288, consisting of 125 boys and 163 girls. The data were collected using questionnaires. The first questionnaire was used to measure the levels of interpersonal competence, while the second one was aimed to assess the levels of sex role. The data were analyzed statistically by the use of Product Moment and analysis t-test. The research findings showed that there was a positive relationship between the degree of sex role and the levels of interpersonal competence of adolescence rxy 0,170, high significance 0.000. Furthermore, the androgyny had a higher level of interpersonal competence of adolescence than the uncategorized (androgyny mean 145.69 and uncategorized mean 133.07), and the girls had a higher level of interpersonal competence than the boys (mean 146, and 151.07).